Pengaruh Struktural Economic, Resource, Dan Social Content terhadap Kepercayaan dan Kepuasan serta Komitmen dan Relationship Intention Nasabah - Mohamad Dimyati (Jurnal Aplikasi Manajemen, 2012)
The objective of the research was tested the effect of economic content, resource content, and social content toward trust, satisfaction and customer commitment as well as relationship intention customers of commercial bank government in Banyuwangi Regency. The sample size was 180 respondents. A purposive sampling with disproportional allocation was used to determine the sample of each bank (BRI, BNI, and Bank Mandiri) branch office Banyuwangi. The technical analysis applied to test the research hypothesis was SEM with the support of Amos 5 Program. The result of the research prevailed that there were positive and significant relationships among economic content and trust, economic content and satisfaction, resource content and trust, resource content and satisfaction, social content and trust, social content and satisfaction, trust and commitment, satisfaction and commitment, and commitment and relationship intention.Keywords: economic content, resource content, social content, trust, satisfaction, commitment, relationship intention